HOPE IN CONTEMPORARY PHOTOGRAPHY: THE PORTRAIT OF SELLERS OF GOODS AND SERVICES DURING A PANDEMIC - Ranu Putra, Rahmad Rian (Institut Seni Indonesia Padangpanjang, 2024)
It has been more than 2 years since the covid-19 pandemic struck the world, affecting many aspects ranging from economics to education. As time went on, new habits began to be implemented in people's daily activities, or what is known as the New Normal, such as the obligation to wear masks and wash hands during activities. Departing from here, there is a feeling of longing that arises when communicating and interacting with the community. The mandatory use of masks during the New Normal era makes it difficult to guess the expressions or facial expressions of the other person. The media, which is rife with reports about the spread of covid-19, is also a factor that makes people wary of one another, which makes caring for others not like it used to be. In this case, the worker makes the seller of goods and services an object of work, which is the party that has been negatively affected by the covid-19 pandemic in the economic sector. Portrait photography is a representation of the similarity of human figures in a two-dimensional form. Portrait photography provides a personal indication of both the portrait owner and the portrait subject. Portrait photography is used as a media approach in the cultivation of works for sellers of goods and services in Bukittinggi. With the medium of portrait photography, it brings the artist closer and lets him know how life and problems are felt by sellers of goods and services in Bukittinggi, which are then presented in the form of contemporary photography works. Contemporary photography is part of art photography that is influenced by modernization and is not bound by conventional rules.